Effect of a calorie-restricted, low-glycemic diet and exercise with omega-3 fatty acid and vitamin D supplementation on the risk of metabolic syndrome. Issue 5 (2017) - Thomas, Robert B; Curtis, Amy; Snook, Laelie A; Meckling, Kelly A
No abstract available